The Effects of Interest Rates on Macro-Economic Variables: 2006-2018 Turkey Case - Oğuz Bal (International Journal of Control and Automation, 2020)
Interest rates play a decisive role in the structuring of economic policy. This role is active in the analysis of macroeconomic variables such as savings, investment and GNP. Fund movements required for global and local investments are realized according to the interest and inflation rates in the countries. In this way, individual and organizational behaviors are affected economically. . Interest rates; It is a concept of primary importance in the theoretical studies of economists belonging to schools such as Classical, Neo-Classical, Keynesian, Post Keynesian, Monetarist and Rational Expectations Theory. The fact that it is a concept that policy makers should constantly consider also requires intensive work on the subject.With this study; Considering the theoretical discussions on the determination of the interest rate, which is a monetary policy tool, it is aimed to reveal its key role in the Turkish economy between 2006-2018 in the light of some economic indicators. This study, which is presented methodologically with deductive and descriptive analysis method, will provide a theoretical contribution to researchers working on the Turkish Economy.